(untitled) (Perspectivas em Ciência da Informação, 2009)
The presence of discussions on issues relating to ethics in Brazilian scientific production of Librarianship and Information Science is the main focus of this text, which comes from the periodic review of these fields of knowledge and professional practice. For this reason, picked up a scientific periodical title for each brazilian administrative region, whose editing had been maintained regularly over the period 1997 to 2006. In each of these periodical titles, from keywords previously defined, have been identified articles and essays which addressed the theme. With this, trying to be informed of the reasons for philosophical and doctrinal, the themes and approaches and trends of the discussion Ethics in regular production of Brazilian Librarianship and Information Science. Methodologically, the work involved identification of journals and texts published on the subject, reading and description of them; identification of the aspects highlighted in the objectives pursued, analysis of speech using the technique of Discurso do Sujeito Coletivo collective subject of discourse) - DSC; organization of the ideas contained, aiming to reach a synthesis. We found 10 texts produced by 16 authors, 2 of 1997, 4 in 2005, 4 distributed from 1998 to 2004 and none was found regarding the year 2006. They were identified as ethical foundations, the doctrines of Ethics of Speech, the Ethics of Otherness and Ethical-Political Theory of Justice, in addition to the issues, approaches and trends of the discussion Ethics, which show the issue of professional attitude determined by the current picture of society and current technologies. We conclude that although there is concern about the ethics issue by some of the professionals who write and publish information on the subject, it is still little explored in literature and is more focused on general issues.